From head to toe : body math. - Time-Life for Children (Firm) (Alexandria, Va. : Time-Life for Children, 1993)
A collection of original stories, poems, riddles, games, and hands-on activities to develop early math skills, focusing on math intrinsic to the human body.
Keywords: Mathematics; Human body; Mathematics; Mathematical recreations; Human body